2016
DOI: 10.11138/ccmbm/2016.13.3.204
|View full text |Cite
|
Sign up to set email alerts
|

�Atypical� atypical femur fractures and use of bisphosphonates

Abstract: SummaryBackground. Atypical femur fractures (AFFs) present a rare but serious condition associated with use of bisphosphonates. Underlying mechanisms and clinical risk factors remain unclear. According to the diagnostic criteria formulated by the ASBMR, a lateral localization of an AFF is required. Case history. We present a patient who developed bilateral leg pain while using an oral bisphosphonate and aromatase inhibitor in the course of adjuvant treatment for breast cancer. Initially she was diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…These findings suggest that the lateral cortex should be the main focus when evaluating the extended femur scan for AFFs, which are by definition located on the lateral cortex, although medially located AFFs have previously been reported. (28,29) Our results are in line with the few studies on this topic so far. A case description in 2010 first suggested that an extended femur scan on DXA corresponds with radiologic characteristics of AFF on a bone scintigraphy, computed tomography, and conventional radiography.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings suggest that the lateral cortex should be the main focus when evaluating the extended femur scan for AFFs, which are by definition located on the lateral cortex, although medially located AFFs have previously been reported. (28,29) Our results are in line with the few studies on this topic so far. A case description in 2010 first suggested that an extended femur scan on DXA corresponds with radiologic characteristics of AFF on a bone scintigraphy, computed tomography, and conventional radiography.…”
Section: Discussionsupporting
confidence: 91%
“…Because very subtle cortical irregularities cannot with certainty be discarded as AFF, screening by DXA may lead to unnecessary X‐rays as was the case in 3 of our patients with focal irregularities of the medial cortex. These findings suggest that the lateral cortex should be the main focus when evaluating the extended femur scan for AFFs, which are by definition located on the lateral cortex, although medially located AFFs have previously been reported …”
Section: Discussionmentioning
confidence: 78%
“…It is known that they change the bone matrix composition, which lead to highly mineralized collagen. This may result in a generalized suppression of bone to remodel, leading to the accumulation of micro-damage, and this could affect the intracortical repair and ultimately lead to a complete stress fracture [7] .…”
Section: Discussionmentioning
confidence: 99%
“…The studies with alendronate and risedronate show that patients with osteoporosis will have an anti-fracture effect for at least 5 years. Continued usage over 5 years needs annual re-evaluation, considering factors such as fracture history, BMD, newly diagnosed disorders, other medications known to affect skeletal tatus [2][3][4][5][6] and as in our case, the appearance of radiographic features such as cortical thickening and some clinical features such as the appearance of prodromal symptoms like aching pain in the thigh [7]. For those patients who are considered to have moderately-elevated risk fracture, continuation of BP therapy should be strongly considered [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent concern has arisen about the association between the use of BPs and the appearance of atypical femur fractures (AFF), a rare type of atraumatic or minimal trauma femur fracture occurring below the great trocanter [2]. This rare complication, with a rate of 3.2-50 cases per 10,000 person-years, may be due to the prolonged half-life of BP and their effect on fracture remodelling, although there is not a final explanation for the physiopathology of these fractures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%